2016
DOI: 10.3126/ijssm.v3i2.14670
|View full text |Cite
|
Sign up to set email alerts
|

Performance Appraisal for Employee Development: Exploring Perceptions of Supervisors

Abstract: The purpose of the present study was to explore the perceptions of supervisors on performance appraisal in relation to employee development adopting a qualitative design. In line with its research objective, data obtained from semi-structured interviews conducted with 14 supervisors from the proposed 10 model technical schools and the head office of the Council for Technical Education and Vocational Training (CTEVT), Nepal was analysed. The study brought forth that supervisors perceived the existing performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The usefulness of performance appraisal or its importance as been opined by Bhurtel and Adhikari (2016) is to help organisation allocate its resources, provide feedback mechanism to employees on their performances, maintain working relationship in their team and reward them accordingly within the fair and equal working rules and regulations. Performance appraisal systems should help to develop the employees for the overall organisational objectives.…”
Section: Conceptual Review the Concept Of Performance Appraisalmentioning
confidence: 99%
“…The usefulness of performance appraisal or its importance as been opined by Bhurtel and Adhikari (2016) is to help organisation allocate its resources, provide feedback mechanism to employees on their performances, maintain working relationship in their team and reward them accordingly within the fair and equal working rules and regulations. Performance appraisal systems should help to develop the employees for the overall organisational objectives.…”
Section: Conceptual Review the Concept Of Performance Appraisalmentioning
confidence: 99%
“…The existing research on PA and HRD has primarily focused on these aspects separately, without exploring their potential integration. Several studies in Nepal and internationally have examined the effectiveness of PA systems and identified issues such as technical and cultural challenges (Mainali, 2010), factors affecting the accuracy of performance evaluation (Pandey, 2019), and employees' perception of satisfaction and outcomes related to PA (Bishowkarma, 2017;Bhurtel& Adhikari, 2016;Pudasaini, 2013;Sharma, 2018).…”
Section: Review Of the Literature And Hypothesis Developmentmentioning
confidence: 99%